Problem-based versus conventional curricula: influence on knowledge and attitudes of medical students towards health research. - Hassan Khan; Ather M Taqui; Muhammad Rizwanulhaq Khawaja; Zafar Fatmi (PLoS ONE, 2007)
BACKGROUND: Medical education curricula in developing countries should emphasize training in health research. This study compares the knowledge and attitudes towards health research between undergraduate medical students undertaking Problem Based Learning (PBL) versus conventional Lecture Based Learning (LBL). METHODS: Two groups comprising 66 (LBL) and 84 (PBL) 4(th) and 5(th) year students from the medical college of Aga Khan University were administered a structured and validated questionnaire. Knowledge and attitudes of the two groups were recorded on a scale (graduated in percentages) and compared for statistical difference. RESULTS: PBL students scored 54.0% while LBL students scored 55.5% on the knowledge scale [p-value; 0.63]. On the attitudes scale, PBL students scored 75.5% against a 66.7% score of LBL students [p-value; 0.021]. A higher proportion of PBL students (89%) had participated in research activities compared to LBL students (74%) and thus felt more confident in conducting research and writing a scientific paper. CONCLUSION: The PBL students showed slightly healthier attitudes towards health research compared to LBL students. Both groups demonstrated a similar level of knowledge about health research. The positive impact of the PBL curriculum on attitudes of medical students towards health research may help in improving research output from developing countries in future.